2021
DOI: 10.3390/toxins13030212
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Toxicogenetic Profiling of Clostridium perfringens in Buffalo and Cattle: An Update from Pakistan

Abstract: Clostridium perfringens is a Gram-positive bacterium that possess seven toxinotypes (A, B, C, D, E, F, and G) that are responsible for the production of six major toxins, i.e., α, β, ε, ι, CPE, and NetB. The aim of this study is to find out the occurrence of toxinotypes in buffalo and cattle of Punjab province in Pakistan and their corresponding toxin-encoding genes from the isolated toxinotypes. To accomplish this aim, six districts in Punjab province were selected (i.e., Lahore, Sahiwal, Cheecha Watni, Bhakk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
1
1
Order By: Relevance
“…In this study, the positive rate of C. perfringens was 19.35% (144/744), which is lower than that of 45% of Tibetan sheep in Gansu and Qinghai regions of China ( 23 ), 65.42% of cattle in Pakistan ( 24 ), 69.7% cattle and 61.5% in Egypt ( 25 ), closing to the cattle (20.8%) and goats (18.3%) in northeast India ( 26 ). Moreover, several studies have shown the varying prevalence of C. perfringens in chickens, pigs, poultry, buffalo, and sheep ( 27 , 28 ).…”
Section: Discussioncontrasting
confidence: 55%
“…In this study, the positive rate of C. perfringens was 19.35% (144/744), which is lower than that of 45% of Tibetan sheep in Gansu and Qinghai regions of China ( 23 ), 65.42% of cattle in Pakistan ( 24 ), 69.7% cattle and 61.5% in Egypt ( 25 ), closing to the cattle (20.8%) and goats (18.3%) in northeast India ( 26 ). Moreover, several studies have shown the varying prevalence of C. perfringens in chickens, pigs, poultry, buffalo, and sheep ( 27 , 28 ).…”
Section: Discussioncontrasting
confidence: 55%
“…Visual assessment of subtype patterns leads to deduce the relatedness (band difference) when in fact the isolates were obtained in different cities of Pakistan. Khan et al(43) and Nasir et al (44) also confirmed the incidence of epsilon toxin causing eneterotoxemia in bovine species of Pakistan origin, which could be a major threat in the near future.…”
mentioning
confidence: 84%